2020
DOI: 10.1111/spc3.12555
|View full text |Cite
|
Sign up to set email alerts
|

Attitude strength: Distinguishing predictors versus defining features

Abstract: Attitudes play a fundamental role in many aspects of social psychology, but researchers have long recognized that attitudes vary in their susceptibility to change and their influence on behavior and cognitive processes. This insight lies at the heart of attitude strength, which is defined as an attitude's durability and impact. A variety of attitude attributes such as certainty and ambivalence have been shown to correlate with these aspects of attitude strength, which has made for some confusion as to what var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 103 publications
2
52
0
Order By: Relevance
“…These findings add to a growing body of work suggesting that emotionality deserves to join the pantheon of attitude-strength predictors. To be considered a predictor of strength, a construct should be associated with an attitude’s influence and durability (Krosnick & Petty, 1995; Luttrell & Sawicki, 2020). Prior evidence linking attitude emotionality with accessibility (Rocklage & Fazio, 2018)—a key indicator of attitude strength—and emotionality’s effects on intentions and behavior (Lavine et al, 1998; Lawton et al, 2009) meets the former condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings add to a growing body of work suggesting that emotionality deserves to join the pantheon of attitude-strength predictors. To be considered a predictor of strength, a construct should be associated with an attitude’s influence and durability (Krosnick & Petty, 1995; Luttrell & Sawicki, 2020). Prior evidence linking attitude emotionality with accessibility (Rocklage & Fazio, 2018)—a key indicator of attitude strength—and emotionality’s effects on intentions and behavior (Lavine et al, 1998; Lawton et al, 2009) meets the former condition.…”
Section: Discussionmentioning
confidence: 99%
“…Because we are proposing a novel predictor of attitude stability, it is useful to show that emotionality is not redundant with other common predictors of attitude strength. Thus, in Study 2b, we aimed to replicate these results and examine whether emotionality uniquely predicted stability even when controlling for other commonly measured attitude-strength predictors, including those often associated with thoughtful attitudes (knowledge, certainty, ambivalence; see Luttrell & Sawicki, 2020). In Study 2c, we aimed to replicate Study 2b in another population (college students).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it may surprise some readers that other strength-related attitude attributes such as ambivalence and importance did not emerge as robust predictors of attitude stability. Although these variables are often described as reliable predictors of attitude strength, prior evidence has been mixed, and these variables’ effects on attitude strength are often moderated by other features of the attitude or situation (see Luttrell & Sawicki, in press). Nevertheless, even though attitude certainty has sometimes failed to predict attitude stability (e.g., Craig et al, 2005), we find pretty consistent evidence for its role in predicting stable attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on attitude stability has been conducted within the context of the attitude strength literature. Strong attitudes are those that influence thoughts and action and remain durable over time and in the face of persuasive information (Krosnick & Petty, 1995; Luttrell & Sawicki, in press). Past research has identified myriad variables that predict an attitude’s strength, including how important an attitude is (Eaton & Visser, 2008), how much someone recognizes both positive and negative qualities of the object (i.e., “ambivalence”; Armitage & Conner, 2000), and how confident someone is about their attitude (Tormala & Rucker, 2018).…”
Section: Attitude Stabilitymentioning
confidence: 99%
“…A person's attitude toward a product or service (i.e., his or her summary evaluation) has long been shown to reliably predict behavior and intentions, especially when that attitude is strong (Luttrell & Sawicki, 2020;Petty & Krosnick, 1995). One reliable way to identify strong attitudes is to measure people's metacognitive assessments of their attitudes (Fabrigar, Wegener, & MacDonald, 2009), where metacognition refers to people's evaluations or perceived qualities of their own thoughts (Petty, Briñol, Tormala, & Wegener, 2007).…”
Section: Attitude Moralizationmentioning
confidence: 99%